The Importance of Social and Emotional Learning in Student Success: A Mixed Methods Research Study - Hafiz Muhammad Afzal Haroon; Sobia Nageen; Prof. Dr. Salman Masood Sheikh; Muhammad Imtiaz (Journal of Peace, Development and Communication, 2023)
This mixed methods research study investigates the significance of social and emotional learning (SEL) in fostering student success. The study aims to explore the relationship between SEL and academic achievement by utilizing both quantitative and qualitative approaches. Through surveys and interviews, the research examines the extent to which SEL skills contribute to overall student well-being and academic performance. The findings highlight the multifaceted impact of SEL on student success and provide insights for educators, policymakers, and stakeholders seeking to enhance educational practices, it emphasizes the necessity of integrating SEL into educational curricula and provide insights into the most effective strategies for its implementation.